2019
DOI: 10.1002/lary.28364
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Estrogen Receptor Beta in Idiopathic Progressive Subglottic Stenosis

Abstract: Background/ObjectivesIdiopathic progressive subglottic stenosis (IPSS) predominantly affects females in perimenopause. It has, therefore, been hypothesized that estrogen is involved in its pathogenesis. There are two main types of estrogen receptors: ER‐α and ER‐β. Abnormal variants of ER‐β have previously been shown to be associated with poor wound healing. Estrogen receptors have recently been identified in subglottic tissue samples, with elevated levels of ER‐α and progesterone receptors, and no expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…No definitive cause of iSGS has been identified, but because the initial presentation often coincides with menopause, the underlying belief is that the disease process is hormonally mediated. [16][17][18] Some evidence suggests that subglottic narrowing and deposition of collagen is mediated by estrogen. 19,20 Certainly, hormonal changes occur during pregnancy as well, thus, presentation during pregnancy would not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…No definitive cause of iSGS has been identified, but because the initial presentation often coincides with menopause, the underlying belief is that the disease process is hormonally mediated. [16][17][18] Some evidence suggests that subglottic narrowing and deposition of collagen is mediated by estrogen. 19,20 Certainly, hormonal changes occur during pregnancy as well, thus, presentation during pregnancy would not be unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The following year, Damrose et al demonstrated the presence of ER‐α and ER‐ß in subglottic tissues using immunofluorescence. Relative to control tissues, iSGS specimens demonstrated a significantly greater intensity of ER‐α in the epithelium, and ER‐ß in the submucosal glands and ducts 45 …”
Section: Idiopathic Subglottic Stenosismentioning
confidence: 83%
“…Relative to control tissues, iSGS specimens demonstrated a significantly greater intensity of ER-α in the epithelium, and ER-ß in the submucosal glands and ducts. 45 These recent studies provide some early support for estrogen activity in the subglottis, with differential receptor expression in iSGS patients when compared to normal controls. Given the well-described impact of estrogen on dermal wound healing, further study is warranted to better define the role of estrogen in the etiology and pathophysiology of iSGS.…”
Section: Estrogenmentioning
confidence: 99%
“…Although iSGS is a diagnosis of exclusion, it interestingly affects a homogenous population of primarily perimenopausal, Caucasian females [ 2 , 8 10 ]. The specific etiology of iSGS remains unclear, however proposed pathophysiological factors include gastroesophageal reflux disease (GERD), upregulation of estrogen receptors in the subglottis, pathogenic bacterial flora, and epigenetic changes to inflammatory constituents of the subglottic mucosa [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%